Development of a K-12 Financial Education Curriculum Assessment Rubric - Herman, Rebecca (RAND Corporation, 2015)
To help school district leaders and teachers make informed decisions about the adoption and use of appropriate K-12 financial education curricula, RAND researchers document the current state of the literature and advance a set of criteria for assessing the content, utility, quality, and efficacy of the curricula.